Cross-border banking and business cycles in asymmetric currency unions - Lena Dräger; Christian R. Proa\~no (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2016)
Against the background of the emergence of macroeconomic imbalances within the European Monetary Union (EMU), we investigate in this paper the macroeconomic consequences of cross-border banking in monetary unions such as the euro area. For this purpose, we incorporate in an otherwise standard two-region monetary union DSGE model a global banking sector along the lines of Gerali et al. (2010), accounting for borrowing constraints of entrepreneurs and an internal constraint on the bank's leverage ratio. We illustrate in particular how rule-of-thumb lending standards based on the macroeconomic performance of the dominating region within the monetary union can translate into destabilizing spill-over effects into the other region, resulting in an overall higher macroeconomic volatility. Thereby, we demonstrate a channel through which the financial sector may have exacerbated the emergence of macroeconomic imbalances within the EMU. This effect may be partly mitigated if the central bank reacts to loan rate spreads, at least relative to the case with constant lending standards. – – Vor dem Hintergrund des jüngsten Immobilienbooms und der darauffolgenden -abschwünge in Ländern wie Spanien und Irland untersuchen wir in diesem Papier die makroökonomischen Konsequenzen grenzüberschreitender Bankaktivitäten in Währungsunionen wie der Euro-Zone. Hierzu berücksichtigen wir in einem ansonsten Standard DSGE-Modell einer Zwei-Regionen-Währungsunion einen Bankensektor-Modul nach dem Vorbild von Gerali et al. (2010), um explizit Kreditrestriktionen gegenüber Unternehmen und eine interne Beschränkung der Leverage Ratio der Banken zu modellieren. Wir veranschaulichen insbesondere, wie unterschiedliche Kreditvergabestandards innerhalb der Währungsunion zu destabilisierenden Spillover-Effekten zwischen den Regionen und wiederum zu einer höheren gesamtwirtschaftlichen Volatilität führen können. Dieser Mechanismus wird modelliert, indem die von den Banken festgelegte Beleihungsquote (loan-to-value ratio, LTV), welche die Banken von den Unternehmen einfordern, in Abhängigkeit gebracht wird zur makroökonomischen Performance der dominierenden Region. Dieser Effekt kann teilweise abgemildert werden, zumindest relativ zu dem Fall mit konstanten Kreditstandards, wenn die Zentralbank auf die Leihzinsspanne reagiert.
urn:nbn:de:101:1-201602195088
Keywords: F41; F34; E52; 330; cross-border banking; euro area; monetary unions; DSGE; monetary policy